Analysis of wedge splitting test on refractory castable via integrated DIC. Issue 16 (December 2016) - Vargas, R.; Neggers, J.; Canto, R.B.; Rodrigues, J.A.; Hild, F.
Abstract: One of the key mechanical properties of refractories is their toughness. The latter can be evaluated via wedge splitting tests. One such test is analyzed herein with an integrated approach to digital image correlation. The position of the crack tip, stress intensity factors and T-stress are estimated on two faces of the tested sample made of a refractory castable during the whole cyclic test. It is shown that the change of energy release rate with the crack length can be determined at each time step of the experiment.